IDENTIFICATION OF SEMANTIC FEATURES OF PHRASAL VERBS IN A PARALLEL CORPUS («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
The scientific, technological and information revolutions of the 20th century, which covered all areas of human knowledge and practice, could not but affect linguistics. We are talking not only about new forms of recording, such as audio or video recording and electronic data storage, but about phenomena that fundamentally change our views and approaches to the functioning of language. In recent years, corpus linguistics has become widespread - a branch of applied linguistics whose goal is the creation and maintenance (using machine media and appropriate access tools) of large arrays of language data.
Keywords: corpus linguistics, parallel corpora, phrasal verbs, semantic structure, phraseological unit.